Farm forestry investment in Ireland under uncertainty - Wiemers, Emily; Behan, Jasmina (Economic & Social Studies, 2004)
This paper develops a model to explain farmers? decision to move from agricultural activities to forestry. Farmers in Ireland have strong links with land and are reluctant to enter into forestry even when the returns from it exceed those from farming. This paper examines whether the reluctance among farmers to plant forestry originates in the nature of forestry investment, which is characterised by the irreversibility of the decision, the uncertainty about future returns, and the ability to delay investment in forestry. In this paper we use a real options method and focus on the contribution of uncertainty in returns and costs to the decision to invest in forestry.
Keywords: Agriculture; Forestry; Decision making; Ireland; Investment